Effects of Music-Integrated Learning Activities on Concentration and Engagement in Early Childhood - Azaari, Santi Restiya Putri; Astuti, Wili (Universitas Muhammadiyah Surakarta, 2025)
This study investigates the effects of integrating music into classroom learning activities on the concentration, focus duration, interest, and task completion of early childhood learners aged 3–5 years at KB Roudhotul Jannah. Limited attention span and frequent distractions in the classroom prompted the need for an intervention that supports emotional regulation and sustained engagement. A mixed-methods approach was employed, combining classroom observations, structured interviews, and documentation. Fifteen children participated in the study using purposive sampling. Observation sheets consisted of four indicators: attention level, focus duration, interest in activities, and task completion. Instrument validity was ensured through expert review by early childhood education specialists. The results revealed that prior to the use of music, most children were only able to maintain their focus for 3-5 minutes, were easily distracted by sounds or peer movements. It showed low engagement in learning activities. After systematically being implemented into classroom routines- through accompanying songs, rhythmic clapping, and soft background music played-significant improvements were observed across all measured aspects. Children with high concentration increased from 13 % to 47%, those with a focus duration of ≥ 7 minutes rose from 7% to 53 %, activities interest grew from 20 % to 67 % and task completion improved from 33% to 87 %. The findings demonstrate that music serves as an effective auditory stimulus for enhancing emotional stability, extending attention span, and improving learning engagement. This study provides novel insight into the systematic integration of music within daily preschool routines, particularly in a rural Indonesian early childhood education setting. Music implementation is recommended as a pedagogical strategy to promote cognitive readiness and emotional regulation in early childhood learning environments.